ASSESSING LEARNER PERFORMANCE THROUGH TASK OUTCOMES - Kalayo Hasibuan; Fadhilatun Khoiriyah; M. Surya Abdi; Putri Adinda; Tri Rahmat Ragil Safaat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Assessing student performance through task outcomes is a crucial approach in task-based learning. Traditional methods often focus solely on final exam scores. In contrast, task-based assessment evaluates the application of knowledge to authentic situations, problem-solving skills, communication, collaboration, and critical thinking. This article uses a narrative literature review method by analyzing various journals, books, and academic sources. The findings indicate that this approach is effective in increasing student motivation, engagement, autonomy, and practical language use. This assessment also provides teachers with a more comprehensive picture of student competencies. However, real challenges remain. Teachers often face challenges related to assessment consistency, time management, and the need for clear rubrics. Therefore, effective implementation requires appropriate teacher training, transparent criteria, and balanced feedback. In conclusion, task-based assessment contributes significantly to improving authentic assessment practices and supporting meaningful learning experiences in the modern classroom.